2023
DOI: 10.5114/ada.2022.119080
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in hidradenitis suppurativa patients: a cross-sectional study among Polish patients

Abstract: Introduction: Hidradenitis suppurativa (HS) is a chronic, recurrent and one of the most debilitating dermatoses. It usually presents with inflamed lesions in apocrine gland-bearing skin areas. There is a limited number of studies on the relationship between HS and depression as well as anxiety. Aim: To evaluate the incidence and severity of depressive and anxiety symptoms among Polish patients suffering from HS. Material and methods: Consecutive patients (N = 114) with HS were included in the cross-sectional s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 17 publications
0
17
0
Order By: Relevance
“…11 The disease is associated with severe socioeconomic consequences, a higher prevalence of depression and anxiety, sleep disturbances, sexual dysfunction, fear of stigmatization and suicide ideation. [12][13][14][15][16][17] The disease also affects patients' families', partners' and caregivers' QoL, frequently preventing them from forming long-lasting relationships with HS patients. 12,18,19 Treatment of HS remains a great challenge for dermatologists, and its result is often unsatisfactory for both the patient and the physician.…”
Section: Discussionmentioning
confidence: 99%
“…11 The disease is associated with severe socioeconomic consequences, a higher prevalence of depression and anxiety, sleep disturbances, sexual dysfunction, fear of stigmatization and suicide ideation. [12][13][14][15][16][17] The disease also affects patients' families', partners' and caregivers' QoL, frequently preventing them from forming long-lasting relationships with HS patients. 12,18,19 Treatment of HS remains a great challenge for dermatologists, and its result is often unsatisfactory for both the patient and the physician.…”
Section: Discussionmentioning
confidence: 99%
“…In case–control studies, the differences between skin diseases and healthy controls are always significant, such as in lichen planus or alopecia areata 5,6 . Although the meta‐analysis by Storer et al 1 found the highest prevalence of anxiety in psoriasis patients, there are recent studies showing higher rates in patients with hidradenitis suppurativa 7 . Older age seems to have a protective effect on skin disease anxiety 8 …”
Section: Figurementioning
confidence: 99%
“…5,6 Although the meta-analysis by Storer et al 1 found the highest prevalence of anxiety in psoriasis patients, there are recent studies showing higher rates in patients with hidradenitis suppurativa. 7 Older age seems to have a protective effect on skin disease anxiety. 8 Biological treatment showed significant efficacy in reducing anxiety in all available studies, but sometimes did not correlate with a change in quality of life.…”
mentioning
confidence: 99%
“…In the light of the above-described clinical manifestations, HS is likely to cause notable psychological distress [11][12][13][14][15]. Moreover, our recent study suggested that reasonable number of HS patients suffered from mental disorders, namely, depression and anxiety [16]. This in turn may lead to difficulties related to satisfaction with life (SWL), and utilization of different types of coping strategies [17].…”
Section: Introductionmentioning
confidence: 99%